Development of a mobile application for vancomycin dosing calculation: A useful tool for the rational use of antimicrobials - Tácio de Mendonça Lima; Millena Padela da Silva; Luan Donato Silva Luz; Thais Cristina Amorim Estevão Soares; Etielle Silvestre Dantas; Gabriela Felix Teixeira; Rafael Henrique de Souza Costa; Sérgio Henrique Monte Santo Andrade (Elsevier, 2022)
Background: Mobile applications (app) provide many benefits for healthcare professionals, making them a useful support clinical decision system. Objectives: To describe the development of a mobile app, CalcVAN, to calculate vancomycin dosage regimens for adult and pediatric patients. Methods: This study is a technological production research to develop a mobile app through the rapid prototyping type for the Android system in the Brazilian context. The mobile app structure was developed in four steps: 1) conception, including the needs assessment, the target audience, the literature search, and the definition of contents; 2) prototype planning, including the definition of topics and writing of modules, the selection of media, and the layout; 3) production of the mobile app, including the selection of multimedia tools, the navigation structure, and planning of environment configuration; and 4) make the mobile app available. Results: The CalcVAN has six screens, containing the vancomycin dosing calculator for adult and pediatric patients based on weight and estimated creatinine clearance parameters. Moreover, the mobile app is free and can be used without internet connection. Conclusions: A free mobile app was developed to calculate vancomycin dosage regimens for inpatients. This tool assists to optimize the vancomycin dosing, contributing to the antimicrobial stewardship.